2010
DOI: 10.3762/bjoc.6.58
|View full text |Cite
|
Sign up to set email alerts
|

New amphiphilic glycopolymers by click functionalization of random copolymers – application to the colloidal stabilisation of polymer nanoparticles and their interaction with concanavalin A lectin

Abstract: SummaryGlycopolymers with mannose units were readily prepared by click chemistry of an azido mannopyranoside derivative and a poly(propargyl acrylate-co-N-vinyl pyrrolidone). These glycopolymers were used as polymer surfactants, in order to obtain glycosylated polycaprolactone nanoparticles. Optimum stabilization for long time storage was achieved by using a mixture of glycopolymers and the non-ionic triblock copolymer Pluronic® F-68. The mannose moieties are accessible at the surface of nanoparticles and avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Sumerlin et al reported the direct atom transfer radical polymerization (ATRP) of 3-azidopropyl methacrylate and the functionalization of the corresponding polymers in the presence of mono-substituted alkynes. 18 Star polymers were realized using the click reaction between an azide-end-functionalized polystyrene, poly (tert-butyl acrylate), or poly(ethylene glycol) precursor and a tris alkyne-functional initiator. 12 Mespouille et al reported the synthesis of amphiphilic and environmental responsive polymer networks by click chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sumerlin et al reported the direct atom transfer radical polymerization (ATRP) of 3-azidopropyl methacrylate and the functionalization of the corresponding polymers in the presence of mono-substituted alkynes. 18 Star polymers were realized using the click reaction between an azide-end-functionalized polystyrene, poly (tert-butyl acrylate), or poly(ethylene glycol) precursor and a tris alkyne-functional initiator. 12 Mespouille et al reported the synthesis of amphiphilic and environmental responsive polymer networks by click chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…16 The azide2alkyne cycloaddition has also been utilized for the synthesis of well-defined acylated polymers with perylenebisimide 17 or mannose units. 18 Star polymers were realized using the click reaction between an azide-end-functionalized polystyrene, poly (tert-butyl acrylate), or poly(ethylene glycol) precursor and a tris alkyne-functional initiator. 19 Pascault and coworkers reported copper-catalyzed step growth click polymerization of a-azide-xalkyne dianhydrohexitol stereoisomers 20 and high T g bio-sourced networks by performing the reaction in the presence of a tailormade symmetrical crosslinker.…”
Section: Introductionmentioning
confidence: 99%
“…Coagulum formation was reduced from 40% to 10% in the S1 system, from 90% to 50% in the S2 system and from 100% to 0% in the S3 system. 36,37 Although the presence of the positively charged TMAEMA units should improve the surfactant properties, TMAEMA contents below 20%, as in S1 copolymer, do not seem to be enough for efficiently stabilizing higher solids contents in emulsion polymerizations. The results suggest that using copolymers with too high hydrophilic fractions and higher HEMAGl contents in the statistical block result in unstable latices.…”
Section: Emulsion Polymerizationsmentioning
confidence: 99%
“…Polymer surfactants based in dextran in the emulsion polymerization process were also reported, with potassium persulfate as the initiator . Their applications in the drug delivery field are well documented . Recently, the original synthesis of linear blocks copolymers based on pullulan with various lengths was reported and their water‐soluble properties were fully investigated .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,7 ] Their applications in the drug delivery fi eld are well documented. [8][9][10][11] Recently, the original synthesis of linear blocks copoly mers based on pullulan with various lengths was reported and their water-soluble properties were fully investigated. [ 12,13 ] This copolymer is composed by a pullulan block (hydrophilic block) and a Jeffamine M2005, which is a ω-amino-PPO-b -PEO diblock copolymer.…”
Section: Introductionmentioning
confidence: 99%